2023
DOI: 10.6018/analesps.515611
|View full text |Cite
|
Sign up to set email alerts
|

Predicting teacher resilience by using artificial neural networks: influence of burnout and stress by COVID-19

Abstract: Background: Resilience in teachers allows them to face difficult situations to recover from adversity and there are gender differences. Likewise, artificial intelligence and the techniques associated with it have proven to be very useful in predicting educational variables and studying the interconnection between them after COVID-19. That said, the general objective of this research was to predict the levels of resilience in secondary school teachers through the design of an artificial neural network (ANN). Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 45 publications
4
10
0
3
Order By: Relevance
“…Likewise, the type of school (public versus subsidized-private) seems to affect student outcomes, and so environmental variables influence the neural network, as in biological models (Berman et al, 2019). Regarding h5, it is confirmed that it is possible to design a model through an ANN capable of predicting the results of a series of variables from the field of educational psychology in the school population, following previous studies carried out with the educational community (Feng & Law, 2021;Martínez-Ramón et al, 2023), suggesting that there is a body of knowledge and evidence to support the feasibility of building this type of model, beyond other fields where its efficacy has also been demonstrated (Badman et al, 2020;Farivar et al, 2020;Gorospe-Sarasúa et al, 2021;Sánchez et al, 2021).…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Likewise, the type of school (public versus subsidized-private) seems to affect student outcomes, and so environmental variables influence the neural network, as in biological models (Berman et al, 2019). Regarding h5, it is confirmed that it is possible to design a model through an ANN capable of predicting the results of a series of variables from the field of educational psychology in the school population, following previous studies carried out with the educational community (Feng & Law, 2021;Martínez-Ramón et al, 2023), suggesting that there is a body of knowledge and evidence to support the feasibility of building this type of model, beyond other fields where its efficacy has also been demonstrated (Badman et al, 2020;Farivar et al, 2020;Gorospe-Sarasúa et al, 2021;Sánchez et al, 2021).…”
Section: Discussionsupporting
confidence: 60%
“…En cuanto a la h5, se confirma que es posible diseñar un modelo a través de una RNA capaz de predecir los resultados de una serie de variables del campo de la psicología educativa en la población escolar, siguiendo anteriores estudios realizados con la comunidad educativa (Feng & Law, 2021; Martínez-Ramón et al, 2023), lo cual sugiere que hay un cuerpo de conocimiento y evidencia que respalda la viabilidad de la construcción de este tipo de modelos, más allá de otros ámbitos donde también se ha demostrado su eficacia (Badman et al, 2020; Farivar et al, 2020; Gorospe-Sarasúa et al, 2021; Sánchez et al, 2021).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…In the field of statistical treatment of these variables, artificial neural networks (ANN) are advanced machine learning techniques that have been used to model and predict various human behaviors and conditions, including the variables of educational psychology [60][61][62]. ANNs are especially useful because of their ability to model nonlinear and complex relationships between predictor and outcome variables, which can be particularly relevant when studying psychological phenomena such as school anxiety [63,64].…”
Section: Introductionmentioning
confidence: 99%